2015
DOI: 10.1136/gutjnl-2014-308553
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism of mitochondrial permeability transition pore induction and damage in the pancreas: inhibition prevents acute pancreatitis by protecting production of ATP

Abstract: Objective Acute pancreatitis is caused by toxins that induce acinar cell calcium overload, zymogen activation, cytokine release and cell death, yet is without specific drug therapy. Mitochondrial dysfunction has been implicated but the mechanism not established. Design We investigated the mechanism of induction and consequences of the mitochondrial permeability transition pore (MPTP) in the pancreas using cell biological methods including confocal microscopy, patch clamp technology and multiple clinically re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
216
2
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(240 citation statements)
references
References 57 publications
11
216
2
11
Order By: Relevance
“…Bile acids, ethanol, and fatty acids were shown to be responsible for around 80% of the etiological factors initiating AP [6]. All of these factors were shown to induce a toxic calcium signal and severe mitochondrial damage in both acinar and ductal cells [3,[7][8][9][10][11]. Importantly, direct administration of ATP (i.e., energy) into the cells restored their functions and prevented cell death [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Bile acids, ethanol, and fatty acids were shown to be responsible for around 80% of the etiological factors initiating AP [6]. All of these factors were shown to induce a toxic calcium signal and severe mitochondrial damage in both acinar and ductal cells [3,[7][8][9][10][11]. Importantly, direct administration of ATP (i.e., energy) into the cells restored their functions and prevented cell death [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…3a,b). Since ATP production through electron transport chain is mediated by ΔΨm and the levels of ATP is directly correlated with the severity of pancreatic injury22. We then tested the effects of compound 1 on ATP production.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that induction of mitochondrial permeability transition pore (MPTP), featured by sudden increased permeability in inner mitochondrial membrane, loss of ΔΨm and impaired ATP production, is the central mechanism of mitochondria-mediated necrosis and the key determinant of injury in various models of AP29. The severity of AP is directly correlated with the extent of necrosis and conversely with the degree of apoptosis in several experimental models of AP922. Saponins from Panax quinquefolium have been shown to prevent MPTP opening and cell injury in a rat myocardial ischemia/reperfusion model30.…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal administration of ethanol plus palmitoleic acid produces pancreatic injury characteristic of alcoholic AP. In this AP model, calcium-dependent mitochondrial dysfunction is shown to mediate ethanol-induced pancreatic injury (Huang et al , 2014; Mukherjee et al , 2016). In future studies, we will investigate whether chronic ethanol exposure alters acinar responsiveness to secretagogue or toxin stimulation; we will also determine whether chronic ethanol exposure compromises the mitochondrial function and makes it more susceptible to subsequent insults.…”
Section: Discussionmentioning
confidence: 99%